G98 Exception reporting at great ormond street hospital – building on junior doctors experiences. (12th March 2018) - Manning, GLP; Das, D; Hassell, J; Parish, E; Ottaway, S; Poisson, J; Sharma, S; McCulloch, R
Abstract : Aims: The new English/Welsh Junior Doctor (JD) contract introduces a powerful tool for positive change – the Exception Report (ER). Following a staged introduction, ER has been available to all JDs (including those not in training), throughout Great Ormond Street Hospital (GOSH) since June 2017. Initial rates of ER have been low, with concerns of JD disillusionment. This project aims to improve the number of submitted ERs with secondary analysis of ER outcome. Methods: A process map identified primary drivers of reporting; Educational Supervisor (ES) engagement; and systemic change. Access to ER systems was improved by incorporating with the postgraduate medical education (PGME) smartphone app. ER was decoupled from ES by allocating departmental ER consultant leads. Ideas on local exception causes; barriers to reporting; and potential solutions were obtained from a JD focus group, which aided production of a guideline for ER leads to address ER root causes. After promoting ER at hospital induction, further interventions were targeted by surveying all JDs on personal experience of exceptions; ER processes; and opinions on reporting. Progress was measured by graphing ER numbers, broken down by reporting department. Future change ideas included a PGME-led awareness campaign, including website, e-newsletter, (P), video and podcast facets; publicity of previous work on JD perspectives; creation of a framework, targeted at JDs, encouraging junior-lead solutions when reporting; supplementation of PGME ES resources; and targeted signposting towards currently-available courses and learning resources. Results: 56 ERs were submitted during Mar-Sep 2017, leading to plans to redesign one department's rota, with financial compensation for three JDs in multiple departments. An additional fellow is being recruited into another department following a JD-initiated business case including, amongst other arguments, ER submissions. No fines have been levied. Multiple interventions are ongoing, with monthly plan-do-study-act (PDSA) cycles planned to aid continued improvement, and to ensure all JDs at GOSH feel empowered to submit ERs. Conclusions: ER should be used positively to identify system issues, and early usage at GOSH has demonstrated ER to both support and initiate constructive departmental change. Impact from current interventions is awaited, as departments harness the potential of the ER process.